Big data storage, collection, & protection with Islamic perspective - Ibrahim Ahmed, Ibrahim Nasreldin; Noordin, Mohamad Fauzan (International Journal of Science and Research (IJSR), 2014)
The paper examines the concept of Big Data storage, collection and protection and its Islamic perspective. It also supports the idea of scholars with evidence from the Noble Quran in terms of use. The paper asserts that Big Data in ICT is view in different aspects. These aspects were extensively dwelled with supportive verses from the Holy Quran. The paper concludes by ensuring proper back up is done by all and promoting the good use of Big Data.